Mass Propagation of Conidia from Several Aspergillus and Penicillium Species - Sansing, G. A. (Appl Microbiol, 1973)
A rapid technique is described for propagation, harvest, and purification of gram quantities of conidia of five Aspergillus and six Penicillium species. IMAGES: